2014
DOI: 10.1016/j.pharmthera.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Role for the nicotinic cholinergic system in movement disorders; therapeutic implications

Abstract: A large body of evidence using experimental animal models shows that the nicotinic cholinergic system is involved in the control of movement under physiological conditions. This work raised the question whether dysregulation of this system may contribute to motor dysfunction and whether drugs targeting nicotinic acetylcholine receptors (nAChRs) may be of therapeutic benefit in movement disorders. Accumulating preclinical studies now show that drugs acting at nAChRs improve drug-induced dyskinesias. The general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 132 publications
(163 reference statements)
1
45
0
1
Order By: Relevance
“…This lack of effect on motor deficits is in agreement with previous work showing that cholinergic interneuron activation/ablation, nAChR agonists/antagonist treatment and mAChR antagonist treatment did not modulate lesion-induced motor impairment (Ding et al, 2011; Maurice et al, 2015; Quik et al, 2008; Quik et al, 2014). These data directly show that striatal cholinergic interneuron activation selectively regulates LIDs with no effect on motor impairment.…”
Section: Discussionsupporting
confidence: 92%
“…This lack of effect on motor deficits is in agreement with previous work showing that cholinergic interneuron activation/ablation, nAChR agonists/antagonist treatment and mAChR antagonist treatment did not modulate lesion-induced motor impairment (Ding et al, 2011; Maurice et al, 2015; Quik et al, 2008; Quik et al, 2014). These data directly show that striatal cholinergic interneuron activation selectively regulates LIDs with no effect on motor impairment.…”
Section: Discussionsupporting
confidence: 92%
“…Results showed increased cleaved caspase-3 and reduced BDNF levels, which suggest that the neuronal and astroglial losses provoked by GAL injection are at least in part due to apoptosis pathway. Impairment in the cerebellar cholinergic system has been implicated in several motor diseases, due the involvement of the cholinergic system in movement control [67]. Acetylcholine plays a key role in cell survival, and it has been associated with neurodegenerative diseases [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in Parkinson’s disease cell models, nicotine protects against endogenous substances such as salsolinol and aminochrome that selectively damage dopaminergic cells (Copeland et al 2005, 2007; Das and Tizabi 2009; Ramlochansingh et al 2011; Munoz et al 2012). Similarly in animal studies, including non-human primates, it has been shown that nicotine delays Parkinson’s disease-like symptoms induced by MPTP (Quik et al 2006, 2009, 2014). Moreover, nicotine may also reduce l -Dopa-induced dyskinesia (Quik et al 2014).…”
Section: Nicotinementioning
confidence: 88%
“…Similarly in animal studies, including non-human primates, it has been shown that nicotine delays Parkinson’s disease-like symptoms induced by MPTP (Quik et al 2006, 2009, 2014). Moreover, nicotine may also reduce l -Dopa-induced dyskinesia (Quik et al 2014). A mechanism of nicotine protection against Parkinson’s disease may involve inhibition of astrocyte activation and inflammatory suppression (Liu et al 2012).…”
Section: Nicotinementioning
confidence: 88%